BUILDING MASTERY OF ACCOUNTING LITERATURE THROUGH REFERENCE MANAGEMENT SOFTWARE: MEMBANGUN PENGUASAAN LITERATUR AKUNTANSI MELALUI PERANGKAT LUNAK MANAJEMEN REFERENSI - Muhammad Faisal; Auliffi Ermian Challen; Imelda Sari (Yayasan Education and Social Center, 2021)
The rapid growth of accounting literature in the digital age is a challenge in studying accounting literature. Mastery of scientific literature is an ability that every student wants to have. Responding to the rapid development of accounting literacy, optimizing the use of reference management software should become a habit for students to answer the challenges of the rapid growth of the accounting literature. This article describes a combination method of utilizing a reference management program Mendeley into student lecture courses to help students master the rapidly evolving accounting literature using digital resources. The use of Mendeley software also helps students form annotation skills in compiling citation entries that are comprehensive and effective